Anhydrobiotic cells of the nematocidic agent Tsukamurella paurometabola C-924 - Armando Hernández; Jesús Mena; Nemecio González; Jesús Zamora; Eulogio Pimentel; Eladio Salazar; María del C Sánchez; Carlos Borroto; Alain Moreira; Lourdes Mesa; Eduardo Smith; Viviana Falcón; et al. (Biotecnología Aplicada)
Biological control of nematodes is a valuable alternative to the use of chemical nematicides in agriculture, because of the high negative impact generated by such chemicals in agroecosystems. From the Gram positive bacterium Tsukamurella paurometabola C-924, the bionematicide HeberNem-L™ has been developed, which is presented as a liquid formulation; nevertheless its stability is still low at 4 °C, with a shelf-life time of 6 months. One way to improve the stability of this bioproduct could be the desiccation of the cells, keeping the viability upon rehydration. Considering this aspect, the aim of our work was to obtain anhydrobiotic cells of the strain C-924 using freeze-drying and spray-drying technologies. One of the main results was the obtaining of anhydrobiotic cells of T. paurometabola C-924, with survival rates higher than 60%. In addition, it was shown that anhydrobiotic cells are more stable vacuum-stored at 4 °C, the rehydrated cells having nematicidal activity in field trials; therefore the powder formulation constitutes a good bionematocide candidate for agricultural use. Furthermore, a new methodology and also a mathematical model were developed to evaluate and predict the stability of desiccated bacterial cells.